Whole-body PET tracking of a d-dodecapeptide and its radiotheranostic potential for PD-L1 overexpressing tumors - Kuan Hu; Wenyu Wu; Lin Xie; Hao Geng; Yiding Zhang; Masayuki Hanyu; Lulu Zhang; Yinghuan Liu; Kotaro Nagatsu; Hisashi Suzuki; Jialin Guo; Yundong Wu; et al. (Elsevier, 2022)
Peptides that are composed of dextrorotary (d)-amino acids have gained increasing attention as a potential therapeutic class. However, our understanding of the in vivo fate of d-peptides is limited. This highlights the need for whole-body, quantitative tracking of d-peptides to better understand how they interact with the living body. Here, we used mouse models to track the movement of a programmed death-ligand 1 (PD-L1)-targeting d-dodecapeptide antagonist (DPA) using positron emission tomography (PET). More specifically, we profiled the metabolic routes of [64Cu]DPA and investigated the tumor engagement of [64Cu/68Ga]DPA in mouse models. Our results revealed that intact [64Cu/68Ga]DPA was primarily eliminated by the kidneys and had a notable accumulation in tumors. Moreover, a single dose of [64Cu]DPA effectively delayed tumor growth and improved the survival of mice. Collectively, these results not only deepen our knowledge of the in vivo fate of d-peptides, but also underscore the utility of d-peptides as radiopharmaceuticals.